Development of an Educational Game for Food Capture Based on Augmented Reality Using Face Mesh Detection and Computer Vision - Sadid, Muhammad Arib Umar; Mulyana, Dadang Iskandar; Gunawan, Dedi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This study aims to propose an educational game for newborns around 4 months old who do not yet know how to distinguish objects that should not be put in their mouths. This seems very normal when it occurs during this stage of life, but it should be encouraged with educational tools — because eating objects that are not food can cause choking or suffocation. AR technology provides an interactive and engaging learning environment by overlaying digital information on the physical environment. The game also uses Computer Vision technology such as Face Detection and Recognition to control user interaction based on body movements. By combining computer vision, the game provides a new and dynamic way to increase user engagement, introducing new opportunities for the development of interactive educational games for young children